The Impact of Reading and Spelling Interventions on Students with Learning Disabilities: An Article Review & Analysis - Alnaim, Mariam (Social Science Learning Education Journal, 2017)
The manuscript has delved into a very specific solution in education; that is improving the spelling of students suffering from learning disability by employing reading and spelling interventions. The researchers themselves admitted that their article primarily focused on improving spelling capacity and not any other aspect of learning disability. It is therefore imperative to state that the primary source of knowledge and learning is reading. Reading interventions often bear remarkable results on children that are underperforming or have a learning disability (LD). For instance, a storybook reading intervention exercise remarkably improved vocabularies of underperforming students (Hargrave et al., 2000). The research (2000) is backed by various intervention studies, and is known to bring improvements. The authors of the article hence completely sidelined, except in one case, a very promising avenue of improving spelling ability by using reading intervention. The authors of this article ignored the importance of emotional stability. Emotionally instable students are known to have learning deficiencies. Most of them do not exhibit reading, spelling or writing disabilities per se, but their emotional instability is often complicit in obstructing their learning process. Autistic children, who are otherwise considered special, were not covered in the article. With very little ground breaking research on the topic, this article too kept itself aloof from the crucial issue of autistic children. The article did not give any procedural advice to parents on how to teach or perform the above mentioned procedures at home, where a significant part of learning occurs. Bullying is another contemporary issue which, in worst cases, results in learning disability, but the paper did not mention it. The authors focused mainly on improving spelling capability, ignoring contemporary issues in education administration and leadership associated with learning disability. The article was altogether silent on implications of the research done on educationist and administrators. It did not provide a formal procedure to reap benefits from the findings. Although the research did achieve breakthroughs in overcoming certain disabilities, like spelling improved considerably, it did not present a procedural and refined way for educationist to implement in their institutions. Moreover, the research did not identify a reliable criterion of selecting disabled students; merely accessing schools databases did not elucidate comprehensive segregating measures for educationists.